2007
DOI: 10.1128/jb.01665-06
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the Late Steps of Coenzyme B 12 Synthesis in Salmonella enterica : Evidence that Dephosphorylation of Adenosylcobalamin-5′-Phosphate by the CobC Phosphatase Is the Last Step of the Pathway

Abstract: We report that cobC strains of Salmonella enterica serovar Typhimurium are impaired in the ability to salvage cobyric acid (Cby), a de novo corrin ring biosynthetic intermediate, under aerobic growth conditions. In vivo and in vitro evidence support the conclusion that this new phenotype of cobC strains is due to the inability of serovar Typhimurium to dephosphorylate adenosylcobalamin-5-phosphate (AdoCbl-5-P), the product of the condensation of ␣-ribazole-5-phosphate (␣-RP) and adenosylcobinamide-GDP by the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 60 publications
0
65
0
Order By: Relevance
“…A remarkable example is the presence of a complete biosynthetic pathway for cobalamin, an essential cofactor for OHR metabolism. Indeed, based on the anaerobic pathway described by Roessner & Scott [59] and the cobinamide salvaging pathway studied by EscalanteSemerena and co-workers [43,[60][61][62], all genes were clearly identified in D. restrictus, although it cannot grow without a supply of vitamin B 12 in the medium ( [1]; J. Maillard 2012, unpublished data). The proteomic data obtained here showed that about half of the proteins of the biosynthetic pathway mostly from the upper pathway were not detected, indicating that under the growth conditions applied, D. restrictus used the corrinoid amended and possibly modified according to its needs.…”
Section: Discussionmentioning
confidence: 99%
“…A remarkable example is the presence of a complete biosynthetic pathway for cobalamin, an essential cofactor for OHR metabolism. Indeed, based on the anaerobic pathway described by Roessner & Scott [59] and the cobinamide salvaging pathway studied by EscalanteSemerena and co-workers [43,[60][61][62], all genes were clearly identified in D. restrictus, although it cannot grow without a supply of vitamin B 12 in the medium ( [1]; J. Maillard 2012, unpublished data). The proteomic data obtained here showed that about half of the proteins of the biosynthetic pathway mostly from the upper pathway were not detected, indicating that under the growth conditions applied, D. restrictus used the corrinoid amended and possibly modified according to its needs.…”
Section: Discussionmentioning
confidence: 99%
“…Related to this, TunG, a putative phosphoglycerate mutase with homology to Francci3_2350, is potentially a CobC-type alpha-ribazole-5′-phosphate phosphatase. CobC is involved in the biosynthesis of cobalamin (vitamin B12), wherein the dephosphorylation of adenosylcobalamin-5′-phosphate by the CobC phosphatase is the last step of the pathway (Zayas and Escalante-Semerena, 2007). Since cobalamin is a co-factor for the radical SAM proteins (Tun B), it is quite possible that the TunG promotes the production of cobalamin for its use during the biosynthesis of tumicamycin.…”
Section: Discussionmentioning
confidence: 99%
“…CobZ was also found to have a flavin in the form of a non-covalently bound FAD, two Fe-S centers, and a b-type heme, which was not similar to CobG [51]. It was thought that the final step in the cobalamin biosynthetic pathway in S. typhimurium involved the dephosphorylation of adenosylcobalamin-5′-phosphate, which is catalyzed by CobC and challenges the pathway indicated where CobS catalyzes the condensation of a-ribazole and an Ado-GDP-cobinamide [52]. The gene that reduces cobalt in the aerobic pathway has yet to be identified, but two candidate genes were identified to encode this enzyme, named CobR [53].…”
Section: Vitamin B12 Biosynthesismentioning
confidence: 99%